AEC2015 : implications for investment in ASEAN agriculture - Teng, Paul P.S. (2015)
Successful implementation of the AEC2015 should have a positive impact on ASEAN’s agri-food sector, leading to improved food availability for the region and increased exports. Sadly, early signs are not encouraging. Major constraints apparent on investment need to be addressed.